Microstructure and properties of NiCoCrAlYTa-Cr2O3-Cu-Mo high-temperature wear-resistant coating prepared by APS - ZHANG Ang; GUO Mengqiu; WANG Changliang; ZHANG Mei; YUE Zhen; WANG Tianying; NIE Zixing; GAO Shen (Cailiao gongcheng)
To investigate the effect of the spraying process parameters on the properties of NiCoCrAlYTa-Cr2O3-Cu-Mo high-temperature wear-resistant coating， the coating is prepared by atmospheric plasma spray （APS） process based on the orthogonal experiment. The range analysis method is used to study the primary and secondary relationships of the process parameters on the microstructure， hardness， and bonding strength of the NiCoCrAlYTa-Cr2O3-Cu-Mo coating， and the spraying process parameters are optimized. The optimized process parameters are that the argon flow rate is 50 L/min， the hydrogen flow rate is 12 L/min， the current is 500 A， and the spraying distance is 100 mm. With the optimized spraying process parameters， the microstructure of the coating is very dense， the porosity is lower than 1%， and the average bonding strength， hardness， and average oxidation speed during 50-100 h at 900 ℃ are 70.7 MPa， 543.7 HV， and 0.07302 g/（m2·h）， respectively. In addition， the friction coefficient and wear rate of NiCoCrAlYTa-Cr2O3-Cu-Mo coating are 0.248 and 2.12×10-6 mm3/（N·m） at 800 ℃， exhibiting good friction and wear properties.